PEMETAAN TRIDARMA PROGRAM STUDI TEKNIK SIPIL UNIVERSITAS ISLAM INDRAGIRI DALAM PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Akbar Alfa (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2018)
SDGs is the world program which is agreed by 193 nations in September 2015 consist of 17 goals, 169 targets and 241 indicators in social dimension coverage, economic and environment, law and governance. The purpose of this research is to study which indicators of SDGs that can be supported its achievement by Civil Engineering Department of Islamic University of Indragiri. The study has been done by desk review method; which is collecting data technique and information through checking and data analyzing. Form documents of Civil Engineering Department of Islamic University of Indragiri year 2017; Academic Guidebook, Strategic Plan of Civil Engineering Department of Islamic University of Indragiri, Strategic Plan Documents of Civil Engineering Department of Islamic University of Indragiri and Operational Plan Documents of Civil Engineering Department of Islamic University of Indragiri. Based on desk review, it can be concluded that the Civil Engineering Department of Islamic University of Indragiri could provided the achievement acceleration of 10 goals, 18 targets and 31 indicators